Uganda : Technical Assistance Report-Managing and Preventing Expenditure Arrears. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses recommendation for managing and preventing expenditure arrears in Uganda. There is need to reconcile the verified stock of arrears with those reported in the annual financial statements. The verification for Budgetary Central Government must be completed, and mechanisms for regular reporting and verification of arrears by local government and the broader public sector must be established. It is also recommended to develop and publish an arrears clearance strategy including prioritization criteria, liquidation policy and institutional responsibility for monitoring and clearance of arrears.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet